Tratamento da aterosclerose em camundongos knockout para apolipoproteína E: associação de um doador de óxido nítrico e probióticos - Vidal, Ivynna Suellen Justino (2020)
Atherosclerosis is a progressive vascular inflammation, initiated by the retention of lowdensity lipoprotein (LDL), leading to oxidative stress, decrease nitric oxide (NO) bioavailability and vasodilation, increased vasoconstriction, and arterial obstruction due to the formation of atheroma plaques. Inorganic nitrates and probiotic microorganisms, from exogenous sources, have emerged as alternatives for the formation of NO, reduction in cholesterol levels, reduction of oxidative stress and reduction of atheroma plaques. Thus, pharmacological agents that are capable of improving vascular function are considered promising for combating atherosclerosis. The aim of the study was to evaluate the effects of the association of sodium nitrate (NaNO3) with Lactobacillus plantarum WJL on experimental atherosclerosis. Were used mice, male and female, from C57BL/6 and apoE-/-knockout strains for apolipoprotein E. The mice were divided into five experimental groups: c57 control (C), apoE-/- control (C), apoE-/- Nitrate (N), apoE-/- Probiotics (P) and apoE-/- association (P + N). At the end of the treatment, the animals were euthanized, the blood was collected to perform the total cholesterol test, and the aortic artery was collected for the study of vascular function and histological analysis. Vascular function was assessed by constructing concentration-response curves to acetylcholine (Ach) and also concentration-response curves to PHE. To evaluate the direct response to smooth muscle, concentration-response curves to PHE and relaxation with sodium nitroprusside (SNP) were performed. The apoE-/- C (male: 769±11; female: 816 ± 3.1) animals showed an increase of approximately nine times in cholesterol levels in relation to C57 C (male: 85±2.1; female: 76±26). The apoE-/- N (male: 679±41; fêmeas:619±92) animals showed a reduction in cholesterol levels when compared to apoE-/-C. In atherosclerotic lesions, a reduction in the formation of plaques was identified in apoE-/- P males (1.9±1.3 vs. apoE-/- C: 12±0.97).The apoE-/- C animals (males: Rmax: 91.0 ± 3.69 and EC50: 6.71 ± 0.25; females: Rmax: 83.3 ± 5.10 and EC50: 7.0 ± 0, 15) didn’t present endothelial dysfunction in relation to ACh relaxation when compared to C57 C (males Rmax: 88.8 ± 5.54 and EC50: 7.11 ± 0.12; females: Rmax: 73.2 ± 4.74 and EC50: 7.1 ± 0.27) The treated animals also didn’t present significant differences, apoE-/- P (males: Rmax: 90.2 ± 18.9 and EC50: 7.2 ± 0.24; females: Rmax : 85.9 ± 2.50 and EC50: 7.2 ± 0.29), apoE-/- N (males: Rmax: 99.5 ± 6.65 and EC50: 7.0 ± 0.12; females: Rmax: 84.8 ± 10.5 and EC50: 6.4 ± 0.22), apoE-/- P + N (males: Rmax: 81.1 ± 5.35 and EC50: 7.0 ± 0.10 ; females: Rmax: 83.6 ± 5.22 and EC50: 6.9 ± 0.23. In the PHE response curves, apoE-/- C (males: Rmax: 102 ± 1.41 and EC50: 7.3 ± 0.079; females: Rmax: 101 ± 6.10 and EC50: 6.6 ± 0.31) showed marked endothelial dysfunction with high contractile response when compared to C57 C (males: Rmax: 59.1 ± 5.39 and EC50: 7.0 ± 0.066; females: Rmax: 72.0 ± 10.3 and EC50: 7.2 ± 0.18). In males the dysfunction of the apoE-/- N animals (Rmax: 46.67 ± 4.27 and EC50: 6.7 ± 0.18) and apoE-/- P + N (Rmax: 62.2 ± 7.91 e EC50: 6.9 ± 0.048), were reversed by the treatments. In the absence of endothelium, we observed a reduction in apoE-/- N (Rmax: 90.0 ± 5.66 EC50: 7.3 ± 0.097) and apoE-/- P + N (Rmax: 105 ± 6.98 and EC50: 7.4 ± 0.04) compared to apoE-/- C (Rmax: 145 ± 8.86 and EC50: 7.7 ± 0.06). In females facing the PHE curve with functional endothelium, endothelial dysfunction was reversed in the apoE-/- P groups (Rmax: 67.2 ± 5.41 and EC50: 7.0 ± 0.13) and apoE-/- P + N (Rmax: 78.6 ± 5.05 and EC50: 7.2 ± 0.073) in relation to apoE -/- C (Rmax: 101 ± 6.10 and EC50: 6.6 ± 0.31). In the absence of endothelium, we observed an increase in sensitivity in the apoE-/- N groups (Rmax: 112 ± 7.46 and EC50: 7.9 ± 0.06) and apoE- /-P + N (Rmax: 104 ± 5.57 and EC50: 7.6 ± 0.07) compared to apoE-/- C (Rmax: 117 ± 13.3 and EC50: 6.5 ± 0.28). In response to NPS, we observed a lower sensitivity of vascular smooth muscle in apoE-/- N males (Rmax: 128 ± 12.0 and EC50: 7.6 ± 0.12 vs. apoE-/- C Rmax: 115 ± 7.5 and EC50: 8.3 ± 0.02) and apoE-/- P + N (Rmax: 138 ± 7.3 and EC50: 7.4 ± 0.08) While there were no significant differences in females, between controls C57 C (Rmax: 126 ± 5.5 and EC50: 7.4 ± 0.27) and apoE-/- C (Rmax: 133 ± 11 and EC50: 8.1 ± 0.43) and among the treated groups apoE-/- P (Rmax: 110 ± 3.5 and EC50: 7.6 ± 0.32), apoE-/- N (Rmax: 122 ± 12 and EC50: 7.2 ± 0.04) and apoE-/- N + P (Rmax: 108 ± 1.1 and EC50: 7.2 ± 0.11) in relation to apoE-/- C. It is possible to conclude that the association of NaNO3 and L. plantarum WJL reversed endothelial dysfunction in experimental atherosclerosis in both sexes.